Development and Validation of the Achievement Emotions Questionnaire – Biology - Badesaba; Punita Govil (Science Education International, 2025)
This study was aimed at developing and validating a scale that measures the emotions of secondary school students toward Biology. Before selecting a particular subject, it is very important to measure student’s emotions toward that subject. The emotions were measured in two academic contexts: class-related and learning-related situations. The participants were 840 (410 male and 430 female) secondary school students aged 13–15 years from various schools in the Uttar Pradesh State of India. Two separate scales were constructed. Scale 1 measures secondary school students’ emotions in class-related situations, and scale 2 measures emotions in test-related situations. The psychometric properties of both scales have been tested by factor analysis. Correlation analysis confirms good convergent validity, and Cronbach’s alpha reveals a good internal consistency of the scale. The validity and reliability values show that the tool has all the necessary psychometric properties and can be used for measuring secondary school students’ emotions toward Biology.